Glenohumeral joint muscles strength of the young tennis players - Zuša, A.; Lanka, J.; Cupriks, L. (Journal of Human Sport & Exercise, 2012)
This paper consists from two parts. First is small theoretic review about shoulder and upper arm kinematics, biodynamics in forehand and serve strokes. Second is dedicated to study young tennis players` glenohumeral joint muscles strength peak torque, analyzing an asymmetry level of dominant and nondominant side. Five 11 years old girls, weight 42,6 kg (± 5,1), height 157,8 cm (± 5,8) have participated in study. Tests performed with use of Technogym`s isokinetic device REV-9000. Mode of the testing - isometric muscle contraction. Verbal and visual feedbacks were utilized to increase the motivation of the subjects. Based on the results of this testing we created individual shoulder joint muscular strength models, that reflects peak torque of right and left shoulder flexion and extension, shoulder abduction and adduction, shoulder internal and external rotation.